Behring's Sea and Arctic Ocean from surveys of the U.S. North Pacific Surveying Expedition in 1855 John Rogers commanding and from Russian and English authorities : additions to July 1868 - Rogers, John; Knorr, E. R; Waldecker, Louis ([Washington D.C.], 1880)
Kartta kuuluu A. E. Nordenskiöldin kokoelmaan Kotelossa, liimattu kankaalle